ARCHETYPE IN GRIMM’S CINDERELLA AND RAPUNZEL - masofa, ima (Faculty of Letters, Dr. Soetomo University, 2019)
This article attempts to analyze archetype in Grimm?s Cinderella and Rapunzel that uses comparative studies to find differences and similarities of archetype in Grimm?s Cinderella and Rapunzel. This article uses archetype concepts that two stories have collective unconsciousness that love can solve problem. This article uses comparative studies to find archetype in Grimm?s Cinderella and Rapunzel. The study aims at comparing two different literary works. The results of this article can be formulated as follows: 1) Archetype concepts can be seen in Grimm?s Cinderella and Rapunzel because they have same characters types and themes. The two main characters of two stories face complication from harsh condition but after meeting a prince, their life change better. The themes of two stories are love. 2) Archetype in Grimm?s Cinderella and Rapunzel have similarities and differences. The similarities of the two stories are the two main characters faces complication because of bad women, themes of the two stories are love. Archetype in Grimm?s Cinderella and Rapunzel get resolution by marrying a prince. The differences of two stories are the way of the two main characters to meet a prince. In Cinderella comes to the prince party with fairy?s help and leaves her shoes that lead to prince meets and marries her. In Grimm?s Rapunzel, she meets a prince in a tower by using her long hair. Keywords: Archetype, Collective unconsciousness, Comparative Studies.